A Review of Issues in Gamified Surveys. (April 2017) - Keusch, Florian; Zhang, Chan
The term "gamification" is used for a wide variety of techniques aimed to increase respondent engagement while filling out web surveys. Suggested approaches range from rephrasing questions to sound more game-like to embedding the entire survey into a game where respondent avatars adventure through a fantasy land while answering survey questions. So far, only a few experimental studies regarding the influence of gamification on survey responding have been published in peer-reviewed journals. This article systematically reviews the current research literature on gamification in surveys by first answering the question as to what gamification entails in the context of web surveys by identifying relevant gamification elements. Next, the article discusses how these elements could influence survey data quality using the Total Survey Error framework. Finally, a systematic review of empirical evidence on gamified surveys from published and unpublished studies is provided. While most studies found in our literature review reported a positive effect of using game elements, such as challenges, story/narrative, rewards, goals/objectives, and badges, on psychological outcomes among survey respondents (e.g., fun, interest, satisfaction), the influence of these elements on behavioral outcomes (e.g., completion and break-offs, item omission, satisficing, responses) and, therefore, survey quality is more unclear. This article informs survey researchers and practitioners of the current state of research on survey gamification and identifies potential areas for future research.